Common variants at 12q14 and 12q24 are associated with hippocampal volume - Bis, Joshua C.; Schnell, Knut (Nature genetics, 2012)
Aging is associated with reductions in hippocampal volume that are accelerated by Alzheimer's disease and vascular risk factors. Our genome-wide association study (GWAS) of dementia-free persons (n = 9,232) identified 46 SNPs at four loci with P values of <4.0 × 10−7. In two additional samples (n = 2,318), associations were replicated at 12q14 within MSRB3-WIF1 (discovery and replication; rs17178006; P = 5.3 × 10−11) and at 12q24 near HRK-FBXW8 (rs7294919; P = 2.9 × 10−11). Remaining associations included one SNP at 2q24 within DPP4 (rs6741949; P = 2.9 × 10−7) and nine SNPs at 9p33 within ASTN2 (rs7852872; P = 1.0 × 10−7); along with the chromosome 12 associations, these loci were also associated with hippocampal volume (P < 0.05) in a third younger, more heterogeneous sample (n = 7,794). The SNP in ASTN2 also showed suggestive association with decline in cognition in a largely independent sample (n = 1,563). These associations implicate genes related to apoptosis (HRK), development (WIF1), oxidative stress (MSR3B), ubiquitination (FBXW8) and neuronal migration (ASTN2), as well as enzymes targeted by new diabetes medications (DPP4), indicating new genetic influences on hippocampal size and possibly the risk of cognitive decline and dementia.